2020
DOI: 10.1371/journal.pbio.3000657
|View full text |Cite
|
Sign up to set email alerts
|

The receptor tyrosine kinase Ror is required for dendrite regeneration in Drosophila neurons

Abstract: While many regulators of axon regeneration have been identified, very little is known about mechanisms that allow dendrites to regenerate after injury. Using a Drosophila model of dendrite regeneration, we performed a candidate screen of receptor tyrosine kinases (RTKs) and found a requirement for RTK-like orphan receptor (Ror). We confirmed that Ror was required for regeneration in two different neuron types using RNA interference (RNAi) and mutants. Ror was not required for axon regeneration or normal dendri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 80 publications
1
34
0
Order By: Relevance
“…We have recently shown that Patronin-mediated minus-end growth is an important regulator of dendritic microtubules in Drosophila [77], so it is possible that microtubule severing in conjunction with Patronin recruitment to minus ends can compensate for nucleation under most normal circumstances. Consistent with this hypothesis, phenotypes from reduction of nucleation or Patronin become more evident after severe stress, including axon [29] or dendrite [77,98] injury.…”
Section: Plos Biologymentioning
confidence: 56%
See 1 more Smart Citation
“…We have recently shown that Patronin-mediated minus-end growth is an important regulator of dendritic microtubules in Drosophila [77], so it is possible that microtubule severing in conjunction with Patronin recruitment to minus ends can compensate for nucleation under most normal circumstances. Consistent with this hypothesis, phenotypes from reduction of nucleation or Patronin become more evident after severe stress, including axon [29] or dendrite [77,98] injury.…”
Section: Plos Biologymentioning
confidence: 56%
“…Modulating Wnt signaling could therefore influence neuroprotection in dendrites. In addition, we have found that this pathway is required during dendrite regeneration to position nucleation sites in regrowing dendrites [98]. Interestingly, G protein coupled receptors (GPCRs) represent 33% of all Food and Drug Administration-approved drug targets, and as part of this family, fz presents a possible target [82].…”
Section: Plos Biologymentioning
confidence: 99%
“…However, it was only recently shown that neurons survive removal of all dendrites and can regrow a new arbor ( Stone et al , 2014 ). Only a handful of genes including Akt ( Song et al , 2012 ) and Ror ( Nye et al , 2020 ) have been linked to dendrite regeneration. To identify dendritic RAGs, we isolated RNA from Drosophila neurons after in vivo dendrite removal.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study in Drosophila C4da neurons has identified the receptor tyrosine kinase-like orphan receptor (Ror) as a critical factor for dendrite regeneration after injury (Nye et al, 2020 ). Subsequent studies suggest that Ror promotes TM nucleation for dendritic branch growth in cooperation with the Wnt signaling pathway (Nye et al, 2020 ; Weiner et al, 2020 ).…”
Section: Spatial Control Of Dendrite Remodelingmentioning
confidence: 99%